Hubungan Kondisi Fisik Rumah, Tempat Perindukan dan Perilaku dengan Kejadian Demam Berdarah Dengue - Herdianti, Herdianti; Sembiring, Firdaus Yustisia; Husein, Alhafez; Rahayuningtyas, Arimby (Jurnal Kesehatan Komunitas, 2025)
The dengue virus that causes dengue hemorrhagic fever (DHF) is spread by the Aedes aegypti and Aedes albopictus mosquitoes. The aim of this study was to examine the relationship between physical conditions of the home and behavior with the incidence of dengue fever. This research is a quantitative study using a cross-sectional research design. Data collection was conducted from May to June 2024. The population in this study was all residents in the Sei Langkai Community Health Center Working Area in 2024. In this study, there were 183 respondents using questionnaires and observation sheets conducted through interviews and observations. The sampling technique in the study used simple random sampling. The statistical test used was the chi-square test. Data were analyzed univariately and bivariately. The results of this study indicate a relationship between ventilation with wire mesh (p value = 0.046) and water reservoirs (p value = 0.046) with the incidence of dengue fever. Meanwhile, room lighting (p value = 0.814), residential density (p value = 0.063), the habit of hanging clothes (p value = 0.063) and the habit of using anti-mosquito lotion (p value = 0.249) are not related to the incidence of dengue fever. The conclusion of the study of the physical condition of the house (ventilation with wire mesh) and breeding places (water reservoirs) has a significant relationship with the incidence of DHF in the Sei Langkai Community Health Center Work Area in 2024. Suggestions to the community are to always clean places that can hold water by implementing 3M Plus covering, draining and burying and recycling.